2020
DOI: 10.3390/molecules25071555
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Induction by Drought Stress in the Calyx of Roselle Cultivars

Abstract: Abiotic factors can alter the chemical profile of crops and the number of compounds they contain. In this study, the anthocyanin and anthocyanidin contents, determined by ultra-performance liquid chromatography (UPLC-MS/MS), and the colour attributes of the calyces of three cultivars of Hibiscus sabdariffa subjected to three water stress regimes during the stage of physiological maturity were investigated. The total anthocyanin content in calyx increased relative to the control content under a 65% moisture irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The ACN composition can vary between different sources and varieties of foods [5], depending on whether they are fresh, frozen or dried [6], with seasonability and environmental stress [7], as well as with food storage and preparation techniques (i.e., peeled, unpeeled) indicating that their presence might be concentrated in specific areas of fruits and vegetables such as the skin or flesh [5,8]. In 2002, the consumption of ACNs was estimated to be 12.5 mg/day/person in the United States, although it is anticipated that this number has risen due to the increased popularity of the so-called 'superfood' market for health and wellbeing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The ACN composition can vary between different sources and varieties of foods [5], depending on whether they are fresh, frozen or dried [6], with seasonability and environmental stress [7], as well as with food storage and preparation techniques (i.e., peeled, unpeeled) indicating that their presence might be concentrated in specific areas of fruits and vegetables such as the skin or flesh [5,8]. In 2002, the consumption of ACNs was estimated to be 12.5 mg/day/person in the United States, although it is anticipated that this number has risen due to the increased popularity of the so-called 'superfood' market for health and wellbeing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that a wide range of environmental stresses can stimulate the production and accumulation of anthocyanins in plants [ 70 , 71 , 72 ], suggesting that these secondary metabolites may be closely correlated with the tolerance of plants to adverse environmental conditions as indicated by earlier studies [ 31 , 33 ]. Although light is required for plants to generate energy for growth and development, there are potential risks in capturing light energy by the photosynthetic apparatus of plants [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 97%
“…Anthocyanins are a group of flavonoid-type secondary metabolites found throughout the plant kingdom. They play a crucial role in plant reproduction by attracting pollinators and seed dispersers through pigmentation in flowers, fruits and vegetative tissues [ 42 ], and they also serve as protectants against a variety of abiotic and biotic stresses [ 23 , 43 , 44 , 45 , 46 , 47 ]. Anthocyanins accumulate in response to abiotic stresses such as drought, cold, and high light intensity.…”
Section: Discussionmentioning
confidence: 99%